Bystander activation of iNKT cells occurs during conventional T-cell alloresponses - Jukes, J; Wood, K; Jones, N (2012)
It is well established that iNKT cells can be activated by both exogenous and a limited number of endogenous glycolipids. However, although iNKT cells have been implicated in the immune response to transplanted organs, the mechanisms by which iNKT cells are activated in this context remain unknown. Here we demonstrate that iNKT cells are not activated by allogeneic cells per se, but expand, both in vitro and in vivo, in the presence of a concomitant conventional T-cell response to alloantigen. This form of iNKT activation was found to occur independently of TCR-glycolipid/CD1d interactions but rather was a result of sequestration of IL-2 produced by conventional alloreactive T cells. These results show for the first time that IL-2, produced by activated conventional T cells, can activate iNKT cells independently of glycolipid/CD1d recognition. Therefore, we propose that the well-documented involvement of iNKT cells in autoimmunity, the control of cancer as well as following transplantation need not involve recognition of endogenous or exogenous glycolipids but alternatively may be a consequence of specific adaptive immune responses. The authors show that iNKT cells are not intrinsically alloreactive but are activated following transplantation through the sequestration of IL-2 produced by recently activated, conventional alloreactive T cells. © copyright 2011 The American Society of Transplantation and the American Society of Transplant Surgeons.